The effect of CaCO3 nanoparticles on mechanical and morphological properties of PLA/CS/CaCO3 composites - Islam, Md. Saiful; Abdullah, Abdul Halim; Mohd Idrus, Muhammad Abdul Mun'aim (WorldConferences.net, 2013)
Blending of chitosan (CS) with suitable polymer matrix is an often used and effective method to improve the physical and mechanical properties of blend composites. In this study, chitosan (CS) natural polymer filled Poly(lactic acid) (PLA) and calcium carbonate (CaCO3) nanoparticles composites were prepared through a solution casting method. The morphological properties of PLA/CS and PLA/CS/CaCO3 composites were investigated with scanning electron microscopy (SEM) and found to be extensively transformed with CS and CaCO3 content. Furthermore, Fourier transform infrared spectroscopy (FTIR) revealed that CaCO3 interacted between PLA and CS in the composites. The mechanical properties of both composites in terms of tensile strength and tensile modulus were significantly improved by the addition of CaCO3 into the matrix. Moreover, both tensile strengths and tensile modulus of the composites showed an increasing trend with increasing CS and CaCO3 content. However, whilst the CS content was increased to 15 wt%, the tensile strength and tensile modulus reduced slightly. The fracture surfaces of blend composites were also recorded using SEM and it was indicated smooth and homogeneous texture throughout the surface of composites.